Harmonizing educational orientation among madrasah students in nigeria: addressing issues in rigidity of Islamic education - Surajudeen, Ahmad Tijani; Awang Mat , Muhamad Zahiri (Association of Malaysian Muslim Intellectuals, 2013)
Madrasah as an institution of learning among Muslims has been questioned and criticized for stagnation and rigidity. Specifically, the challenges of terrorism and insurgency in the northern Nigeria in the last few years, has led to the questionability of Muslim thought and educational orientation in the country. Many contemporary Muslim scholars have extensively discussed the necessity of moderation has manifest in the Qur’an and Hadith as an attempt to address terroristic activities. Despite of the effort so far in preaching against terroristic activities and enlightenment movement on moderation, Nigerian Muslims have not looked inwardly in harmonizing various educational orientations that lead to the emergence of different terroristic thought and insurgencies in the country. The primary objective of this paper is to investigate various educational orientations among the Muslim students in Nigeria in order to address the rigidity of Islamic education. In this paper, three educational orientations are identified namely: traditionalist, fundamentalist and Secularist/Modernist orientations. The paper has argued that, various educational orientations in the past had shown the manifestation of the expansion of Muslims’ horizons, independent thinking and peaceful co-existence. Therefore, it is argued that those educational orientations must be harmonized and unified in order to portray the intellectual competence among the madrasah students positively. It is thereby suggested that, the stake holders and policy makers should constantly review the curriculum of madrasah in order to address the challenges of different educational thought. Also, there should be intellectual forum through which constructive ideas will be shared as an attempt to unify different educational orientations in madrasah context.